Suporte especializado de hardware para geração automática de loop pipelining em FPGAS - Souza, Guilherme Stefano Silva de (2014)
Loop pipelining is a technique that may offer significant performance improvements, being employed not only in conventional compilation targeting microprocessors, but also by High Level Synthesis (HLS) tools, targeting heterogeneous architectures and hardware accelerators. This work presents a specialized hardware support aiming at facilitate compilation tasks for HLS tools, along with potential advantages in execution performance and total silicon area employed. Two specialized hardware modules are presented: a queue register file and an instruction predication control module.